EFEKTIVITAS PELATIHAN PENDIDIK SEBAYA (PEER GROUP) TERHADAP PENGETAHUAN DAN SIKAP SISWA SMA N 1 PADANGSIDIMPUAN TENTANG PENCEGAHAN NAPZA DI KOTA PADANGSIDIMPUAN TAHUN 2016 - Dalimunthe, Enda Mora (Universitas Aufa Royhan, 2016)
NAPZA is the acronym of Narkotika (narcotic), Psikotropika (psychotropic), and Zat Adiktif (addictive substances) which includes natural substances or synthetic which will cause the changes inphysical and psychic functions and will also cause dependence if it is consumed. Teenagers are veryvulnerable to consume narcotic because of their getting pressure from their peer group, their curiosity totry it, and their ego. The objective of the research was to know the influence of the pre and post peer group training onknowledge and attitude of SMA I students at Padangsidempuan about the prevention from NAPZA atPadangsidempuan. The type of the research was quasi experiment with non-equivalent control groupdesign. The population was all 414 tenth and eleventh grade students in the academic year of 2012-2013.The samples were 26 students from Class X (eight classes) and Class XI (five classes). The data wereanalyzed by using univatriate and bivatriate analysis with wilcoxon test. The result of the analysis showed that there was the disparity of the effectiveness of teenagers’knowledge in the treatment group before and after the training with p=0.002, and there was the disparityof effectiveness of teenagers’ attitude in the treatment group before and after the training with p=0.001. It is recommended that the management of SMA Negeri I, Padangsidempuan, perform selfdevelopment program which might be run by an organization so that the students can participate or beinvolved in any school activity, spend their spare time in positive activities, and cooperate with the theirparents in order that their parents will know their children’s success in any competition in the future.